Thermodynamic of dissolution and hydrogen bond of the pyrrole, N-methylpyrrole with proton acceptors - Rakipov, Ilnaz T.; Petrov, Artem A.; Akhmadeev, Bulat S.; Varfolomeev, Mikhail A.; Solomonov, Boris N. (Thermochimica acta, 2016)
[Display omitted] •Enthalpies of solution were measured of amines in 15 proton acceptor solvents.•Enthalpies of solution were measured for 15 proton acceptors in amines.•Enthalpies of NH⋯B hydrogen bonds were calculated for amine with proton acceptors. Enthalpies of dissolution of pyrrole, N-methylpyrrole in proton acceptor solvents and proton acceptors in the medium of pyrrole, N-methylpyrrole were measured. The enthalpies of hydrogen bond of pyrrole, N-methylpyrrole with proton acceptors were calculated from experimental data of solution enthalpy of amines with organic compounds. The hydrogen bond enthalpies of proton acceptors with N- methylpyrrole are equal to zero unlike with pyrrole. The hydrogen bond enthalpies of proton acceptors (B) in pyrrole are significantly lower than the enthalpies of hydrogen bonding of systems of pyrrole-base in the complexes 1:1 due to reorganization effects of pyrrole as solvent. The cooperative effects in multi-particle complexes of pyrrole with bases are negligible.